Associated Age and Weight Before Pregnancy With Chronic Energy Deficiency on Pregnant Women in Moilong District, Banggai Regency - Monoarfa, Yustiyanty; Otoluwa, Anang S; Fandir, Abdul; Basri, Hasan; Reski, Rahayu Nurul; Hadju, Veni (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Pregnant women at risk of developing chronic energy deficiency (CED) are among the victims of malnutrition. Pregnant women who are at risk for CED can disrupt the fetus's growth and development, namely physical growth (stunting), brain development, and body metabolism. Objective : To determine the elements that affect pregnant women's chronic energy insufficiency Research Methods/ Implementation Methods : This cross-sectional study was conducted in Banggai Regency. This study included 101 pregnant women. The dependent variable is CED status, while the independent variable is maternal features. The analysis used univariate and bivariate tests such as the Chi-square test and the Liniear Regression test. Results : This research shows that 24% of pregnant women still experience CED. Then the results of the Chi-square analysis showed that there was a significant relationship between maternal age and maternal weight before pregnancy on the incidence of CED with respective p values 0.023 and 0.001 (p<0.05). The percentage of relationship between the two variables on the incidence of CED is maternal age with an R square value of 0.103 (10.3%) and for maternal weight before pregnancy of 0.690 (69%). Conclusion/Lesson Learned : Determinant factors that influence CED in pregnant women were found, including the age of the pregnant woman and her weight before pregnancy. Furthermore, it was seen that the mother's weight before pregnancy had a large influence of 69% on the incidence of CED and the age of the pregnant woman had a 10.3% influence on the incidence of CED.